Análise de cenários em indústrias de processo usando simulação discreta : uma aplicação em uma indústria de nutrição animal - Maurício, Gabriel Campos (2015)
The quest for increased productivity has become a mantra repeated ad nauseam in many companies immersed in a globalized market. In this context, many computational techniques have becoming more popular, gaining followers, aiding and refining the process of decision-making. Among the various techniques available, the discrete event simulation stands out, as it allows studying the behavior of systems, real or not, in various conditions, allowing hypotheses to be tested without physical and financial resources are used. In the case of the animal feed industry, this technique becomes a very important tool, especially in the short term planning which involves the management of the floor operations. The animal feed industry is part of the agribusiness chain, and as such, has its inputs internationally listed, commodities, thus effectively managing its installed capacity is a strategic advantage for differentiation before the market needs in terms of cost, time and quality. In this sense, the objective of this study was to develop a discrete simulation model to assist the decision-making process on increasing the rate of bagging an animal feed industry, located in the state of São Paulo. For this study it has been used the Arena® software, Rockwell Software, and as a method of research modeling and simulation, and the simulation model development stages followed the methodology proposed by Law and Kelton (2000) and Banks (2010). Data were always collected with the same operator at the same time. As a result of simulation of the proposed model was possible to analyze different scenarios, assessing the dynamics of the system and with the performance indicators the equipment utilization rate, the amount of products produced and the consumption of electricity and natural gas per ton of product produced. Whereas the use of discrete simulation in animal feed industry belonging to the process industry and with hybrid production process, could be used due to the approach proposed by Spieckmann and Stobbe (2012).